High-affinity uptake of noradrenaline in postsynaptic neurones. - al-Damluji, S. (Nature Publishing Group, 1993)
1. Neurotransmitters released from nerve endings are inactivated by re-uptake into the presynaptic nerve terminals and possibly into neighbouring glial cells. While analysing the functional properties of alpha 1-adrenoceptors in the hypothalamus, we observed a high-affinity uptake process for noradrenaline in postsynaptic peptidergic neurones. 2. In primary hypothalamic cell cultures and in a hypothalamic neuronal cell line, [3H]-prazosin bound with high affinity and was displaced by unlabelled prazosin in concentrations of 10(-10) to 10(-7) M. However, at concentrations of unlabelled prazosin above 10(-7) M, there was a paradoxical increase in apparent [3H]-prazosin binding. 3. Methoxamine, an alpha 1-adrenoceptor ligand that is not subject to significant neuronal uptake, displaced [3H]-prazosin but did not cause the paradoxical increase in the apparent binding of [3H]-prazosin. Cooling the cells to 4 degrees C reduced the total amount of prazosin associated with the cells; under these conditions, methoxamine almost completely inhibited [3H]-prazosin binding to the cells. 4. In the presence of desipramine (DMI), unlabelled prazosin displaced [3H]-prazosin as before, but no paradoxical increase in apparent binding was seen above 10(-7) M. 5. The paradoxical increase of [3H]-prazosin binding was not observed in membrane preparations of hypothalamic neurones. These findings indicated that the paradoxical increase in apparent [3H]-prazosin binding was due to a cellular uptake process that becomes evident at high concentrations of the ligand. 6. DMI (10(-5) M) had no effect on the specific binding of [3H]-prazosin.(ABSTRACT TRUNCATED AT 250 WORDS)